Treatment of Acquired Hypothalamic Obesity: Now and the Future - Dimitri, Paul (Frontiers in Endocrinology, 2022)
The hypothalamus is the centre of neuroendocrine regulation of energy homeostasis and appetite. Maldevelopment of, or damage to, the key hypothalamic nuclei disrupts the coordinated balance between energy intake and expenditure leading, to rapid and excessive weight gain. Hypothalamic obesity is compounded by a disruption of the hypothalamic-pituitary axis, sleep disruption, visual compromise, and neurological and vascular sequalae. Amongst suprasellar tumours, craniopharyngioma is the most common cause of acquired hypothalamic obesity, either directly or following surgical or radiotherapeutic intervention. At present, therapy is limited to strategies to manage obesity but with a modest and variable impact. Current approaches include optimising pituitary hormone replacement, calorie restriction, increased energy expenditure through physical activity, behavioural interventions, pharmacotherapy and bariatric surgery. Current pharmacotherapeutic approaches include stimulants that increase energy consumption, anti-diabetic agents, hypothalamic–pituitary substitution therapy, octreotide, and methionine aminopeptidase 2 (MetAP2) inhibitors. Some pharmacological studies of hypothalamic obesity report weight loss or stabilisation but reported intervention periods are short, and others report no effect. The impact of bariatric surgery on weight loss in hypothalamic obesity again is variable. Novel or combined approaches to manage hypothalamic obesity are thus required to achieve credible and sustained weight loss. Identifying aetiological factors contributing hypothalamic obesity may lead to multi-faceted interventions targeting hyperphagia, insulin resistance, decreased energy expenditure, sleep disturbance, hypopituitarism and psychosocial morbidity. Placebo-controlled trials using current single, or combination therapies are required to determine the impact of therapeutic agents. A well-defined approach to defining the location of hypothalamic damage may support the use of future targeted therapies. Intranasal oxytocin is currently being investigated as an anorexogenic agent. Novel agents including those targeting pro-opimelanocortin-C and AgRP/NPY expressing neurons and the MC4 receptor may result in better outcomes. This article discusses the current challenges in the management of hypothalamic obesity in children and young people and future therapeutic approaches to increasing weight loss and quality of life in these patients.